Opportunities and challenges of interactive public displays as an advertising medium - José, Rui (2011)
Advertising is often the key element in the business case for public display networks. However, this is still a limited medium in its support for key ad- vertising concepts, such as targeting or impact assessment. This chapter analyses how the evolution of the medium is creating the opportunity for re-shaping adver- tising models for Digital Signage. In particular, we consider how the increasing availability of sensing and interaction opportunities may generate the necessary digital footprints that will help to characterise advertising opportunities in Digital Signage and measure impact. A generic footprint model would enable advertising models to be specified at a higher level of abstraction, enabling them to be applied across global display networks composed by very diverse display types, managed by many different entities, and serving many different purposes. We propose a de- sign space that relates the multiple types of digital footprints that can be generated with multiple modes of campaign targeting and impact assessment, providing the ground for a fundamental shift from advertising based on measuring attention to advertising based on active engagement with people.